2002
DOI: 10.1097/00006676-200207000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 is Overexpressed in Chronic Pancreatitis

Abstract: Our results support the hypothesis that COX-2 may be involved in inflammatory responses in chronic pancreatitis and in the progression of this chronic inflammatory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 25 publications
3
61
1
1
Order By: Relevance
“…During AP, the cell membrane ruptures, intestinal bacteria enter the blood, and circulatory, respiratory, urinary, and digestive system abnormalities occur. The results were consistent with previous reports that systemic inflammatory response syndrome (SIRS) and multiple organ failure (MOF) are caused by AP (Schlosser et al, 2002;Isenmann, Rau, Beger, 2001;Buter et al, 2002). When rheum was administered to the rats, multiple metabolic abnormalities such as the occurrence of amines were not observed, even though several metabolic pathways were impacted.…”
Section: Other Metabolitessupporting
confidence: 91%
“…During AP, the cell membrane ruptures, intestinal bacteria enter the blood, and circulatory, respiratory, urinary, and digestive system abnormalities occur. The results were consistent with previous reports that systemic inflammatory response syndrome (SIRS) and multiple organ failure (MOF) are caused by AP (Schlosser et al, 2002;Isenmann, Rau, Beger, 2001;Buter et al, 2002). When rheum was administered to the rats, multiple metabolic abnormalities such as the occurrence of amines were not observed, even though several metabolic pathways were impacted.…”
Section: Other Metabolitessupporting
confidence: 91%
“…The constitutively expressed COX-1 appears to regulate many normal physiologic functions in several cell types, whereas the inducible COX-2 enzyme mediates the inflammatory response. Aberrant COX-2 expression was initially described in colorectal cancer and has now been detected in many human tumors including breast and pancreatic cancers [33,96]. Epidemiological studies have shown that the risk of developing cancers of the colon, breast, esophagus, and stomach is lowered following the ingestion of nonsteroidal anti-inflammatory drugs (NSAIDs) [71].…”
Section: Importance Of Epigenetic Mechanisms As Targets For Chemoprevmentioning
confidence: 99%
“…Furthermore, NS398, a selective COX-2 inhibitor, reduced the growth of PSCs by PANC-1 CM. Several studies have indicated that COX-2 expression is high in both chronic pancreatitis and PDAC therefore suggesting a potential role in fibrosis (6,29). COX-2 levels are also known to positively correlate with the aggressiveness of PDAC (30) and that blocking COX-2 significantly reduces pancreatic tumor size and metastatic potential (31) in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…By immunohistochemistry (IHC), COX-2 was found to be highly expressed in chronic pancreatitis (6), pancreatic adenocarcinoma (7,(13)(14)(15) and pancreatic intraepithelial neoplasia (PanIN) (16). The expression of COX-2 in chronic pancreatitis is primarily localized in the cytoplasm of pancreatic acinar cells, islet cells, and ductal cells (6), while in pancreatic adenocarcinoma it is localized primarily to cancer cells (7). Transgenic over-expression of COX-2 in the pancreas led to the development of pancreatic fibrosis and even cellular transformation (17).…”
Section: Introductionmentioning
confidence: 99%